2021
DOI: 10.1093/jn/nxab119
|View full text |Cite
|
Sign up to set email alerts
|

Citicoline and Memory Function in Healthy Older Adults: A Randomized, Double-Blind, Placebo-Controlled Clinical Trial

Abstract: Background Supplementation of citicoline (CDP-choline), a naturally occurring mononucleotide, has shown beneficial effects on memory function and behavior in populations with a wide range of impairments. However, few studies have investigated its effect in healthy older populations. Objective The objective of this study was to investigate the effects of citicoline (Cognizin®), on memory in healthy elderly populations with age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 42 publications
(45 reference statements)
0
13
0
3
Order By: Relevance
“…Previous studies showed that choline in the form of neurotransmitter (acetylcholine) plays an important role in the learning and memory. 16 It has been also reported earlier that choline supplementation increase learning and memory function in the fetal that exposes with alcohol. 17 In the present study we used water maze to assess memory function.…”
Section: Behavioral Effectsmentioning
confidence: 69%
“…Previous studies showed that choline in the form of neurotransmitter (acetylcholine) plays an important role in the learning and memory. 16 It has been also reported earlier that choline supplementation increase learning and memory function in the fetal that exposes with alcohol. 17 In the present study we used water maze to assess memory function.…”
Section: Behavioral Effectsmentioning
confidence: 69%
“…Cytidine 5’-diphosphocholine, also known as Citicoline or CDP-choline, is a naturally occurring nucleotide that plays an essential role in phospholipid synthesis [ 36 ]. When provided exogenously, CDP-choline divides into choline and cytidine and serve as substrates for phospholipid synthesis [ 37 ].…”
Section: Reviewmentioning
confidence: 99%
“…Studies have also reported benefits to IR and working memory form taking B. monnieri (Calabrese et al., 2008; Pase et al., 2011; Sadhu et al., 2014; Stough et al., 2008). Mind Lab Pro also contains 250 mg of Citicoline, a substance which has been found to improve memory by increasing specific hormonal levels and activate biosynthesis in the central nervous system to protect cell membranes in healthy and unhealthy populations (Gareri et al., 2015; McGlade et al., 2012; Nakazaki et al., 2021). Nootropics such as Alpha Brain and Noocube also contain B. monnieri and also report benefits to memory.…”
Section: Introductionmentioning
confidence: 99%